1968
DOI: 10.1111/j.2042-7158.1968.tb09697.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of ethanol by Coprinus atramentarius in mice

Abstract: Assessment of toxic manifestations and sleeping times in mice shows that the mushroom Coprinus atramentarius potentiates the action of ethanol when administered orally from 3 to 16 hr before a sub-lethal dose of ethanol. Administration of this mushroom 24 hr before, immediately after or 3 hr after the ethanol causes no potentiation. No similar effect was observed with Coprinus comatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…) S. F. Gray seems to be debatable. Some authors asserted that this species presents no or only a slight danger [Genest et al, 1968;Iancovitz, 19831. Furthermore, some authors recently described it as a potent toxic fungus [Laatsch, 19901 and apparently cases of poisoning have been reported [Trestdil, 19911.…”
Section: The Suspicious Fungi Speciesmentioning
confidence: 99%
“…) S. F. Gray seems to be debatable. Some authors asserted that this species presents no or only a slight danger [Genest et al, 1968;Iancovitz, 19831. Furthermore, some authors recently described it as a potent toxic fungus [Laatsch, 19901 and apparently cases of poisoning have been reported [Trestdil, 19911.…”
Section: The Suspicious Fungi Speciesmentioning
confidence: 99%
“…Mice fed with suspensions of the mushroom followed by ethanol reacted with a * Present address: AB Draco, Fack, S-22101 Lund, Sweden. marked increase in sleeping-time compared to that after ethanol alone (Genest et al 1968). This interaction was accompanied by an increased bloodlevel of acetaldehyde as compared to animals receiving ethanol only (Coldwell et al 1969).…”
mentioning
confidence: 99%
“…Isolation of disulfiram from C. atramentarius (9) was not confirmed (10, 11). Although no disulfiram was detected, recent investigations unequivocally confirmed that polar extracts of C. atramentarius significantly potentiate the action.of ethanol in mice (12,13). Recently, an active constituent isolated from C. atramentarius increased blood acetaldehyde levels in mice (14).…”
mentioning
confidence: 99%